Headquarters-subsidiary relationships: impact of distance - Brandstatt, Anne Sophie (My University, 2017)
In the current area of globalization, Multinational Corporations (MNCs) continue to develop their business abroad. In parallel, the role of subsidiaries has significantly evolved and subsidiaries tend to be more autonomous than in the past, which makes complicated relationships between headquarters and subsidiaries. In this paper, the notions of relationships, cooperation and control are studied. Based on previous researchers, distance is defined and the emphasis is put on four dimensions: cultural, administrative, geographic and economic dimensions. Once these different notions are evaluated, the impact of distance over relationships is questioned. In the empirical part, six managers have been interviewed in person and by phone. They work for three different companies from the sector of mass consumption which have their headquarters in a European country. The main finding of this qualitative research is that distance is a reality. When headquarters use the right tools, distance does not impact relationships. However, means of control can affect relationships: subsidiaries can have the feeling not to be independent, that create frustration or even worst, conflicts. Additionally, the thesis enables to point an important factor which may have a negative impact on relationships: divergence in interest between the headquarters and its subsidiaries.
Keywords: headquarters-subsidiary relationships; Multinational Corporations; distance; cooperation; control; fi=Markkinointi|en=Marketing|; fi=Master's Degree Programme in International Business|